Hint-seeking behaviour of western scrub-jays in a metacognition task - Watanabe, Arii; Clayton, Nicola S. (Animal cognition, 2016)
Metacognitive processes during memory retrieval can be tested by examining whether or not animals can assess their knowledge state when they are faced with a memory test. In a typical foraging task, food is hidden in one of the multiple tubes and the subjects are given an opportunity to check the contents of the tubes before choosing the one that they thought contained food. Following the findings from our previous study that western scrub-jays ( Aphelocoma californica ) can make prospective metacognition judgements, this study tested the scrub-jays’ concurrent metacognition judgements. In a series of experiments, uncertainty about the food location was induced in three ways: by making the baiting process visibly unavailable, by inserting a delay between the baiting and food retrieval, and by moving the location of the bait. The jays looked into the tubes more often during the conditions that were consistent with high uncertainty. In addition, their looking behaviour was associated not with the sight of food but with information about the location of the food. These findings suggest that the jays can differentiate the states of knowing and not knowing about certain information and take appropriate action to complement their missing knowledge.